Drosophila Roc1a encodes a RING-H2 protein with a unique function in processing the Hh signal transducer Ci by the SCF E3 ubiquitin ligase. - Noureddine, M.A.; Donaldson, T.D.; Thacker, S.A.; Duronio, R.J. (Developmental Cell, 2002)
Substrate specificity of SCF E3 ubiquitin ligases is thought to be determined by the F box protein subunit. Another component of SCF complexes is provided by members of the Roc1/Rbx1/Hrt1 gene family, which encode RING-H2 proteins. Drosophila contains three members of this gene family. We show that Roc1a mutant cells fail to proliferate. Further, while the F box protein Slimb is required for Cubitus interruptus (Ci) and Armadillo/beta-catenin (Arm) proteolysis, Roc1a mutant cells hyperaccumulate Ci but not Arm. This suggests that Slimb and Roc1a function in the same SCF complex to target Ci but that a different RING-H2 protein acts with Slimb to target Arm. Consequently, the identity of the Roc subunit may contribute to the selection of substrates by metazoan SCF complexes.